2020
DOI: 10.1071/wf19104
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in wildland firefighter fitness and body composition

Abstract: Hiking with a pack is the highest-intensity task that wildland firefighters (WLFFs) perform during sustained activities related to wildland fire suppression. Firefighters perform this and other tasks together as a crew; this provides a unique model to evaluate select physical and physiological changes in members of working crews over a fire season during extended operations. The objective of this study was to evaluate changes in peak aerobic fitness (VO2peak), sustainable aerobic fitness at the ventilatory thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Therefore, WLFFs may experience fatigue, decreased work rate, and ultimately compromised safety. 6 , 10 , 21 23 …”
mentioning
confidence: 99%
“…Therefore, WLFFs may experience fatigue, decreased work rate, and ultimately compromised safety. 6 , 10 , 21 23 …”
mentioning
confidence: 99%
“…Specifically, step-test HR responses improved, and grip strength remained stable during post-season measurements. While seasonal changes in ventilatory threshold have been noted previously, 23 pre-season ventilatory threshold values for more fit and less fit WLFFs’ tend to converge towards a median value at the conclusion of the season 23 . We know that ingress uphill hiking produces a mean metabolic cost of 22 ± 12 mL kg −1 minute −1 , which closely resembles the metabolic cost required to successfully complete the arduous pack test 3,22 .…”
Section: Discussionmentioning
confidence: 51%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21 However, only a few studies have examined the impact of seasonal wildfire suppression on common health variables. 17,23,24 Preliminary evidence from our research team suggest adverse changes in ventilatory threshold, 23 body composition, 23,24 intrahepatic lipids, 24 and serum lipids 24 may result following a season of wildfire suppression. These untoward alterations in important physiological and health outcomes appear to result despite high levels of daily energy expenditure in this physically active cohort.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The inability to blind subjects to each trial condition is an obvious and inherent limitation in this study. The subjects examined during this simulated study were fit and might not be representative of the entire WLFF community, as studies have shown maximal aerobic capacities below the current investigation (Carballo-Leyenda et al 2018;Gaskill et al 2020). This may have resulted in a protection from alterations in the physiological responses to extended periods of exercise in the heat.…”
Section: Discussionmentioning
confidence: 92%